When Facioscapulohumeral dystrophy Meets Myasthenia gravis: Case Report and Literature Review - Ketabforoush, Arsh; Castoro, Ryan; Arnold, W. David; Barohn, Richard (RRNMF Neuromuscular Journal, 2025)
Simultaneous occurrences of rare disorders are significant diagnostic and management challenges. In this case report, we describe the initial clinical presentation, diagnosis, and management of a 66-year-old man with a history of concurrent facioscapulohumeral dystrophy (FSHD) and myasthenia gravis (MG). He presented at age 54 with longstanding symptoms of facial, scapular, and limb weakness which had previously diagnosed at age 23 as limb girdle muscular dystrophy. He also exhibited new symptoms of ptosis, diplopia, and bulbar muscle weakness. Genetic testing and acetylcholine receptor autoantibody testing confirmed the diagnoses of both FSHD and MG. This report discusses the diagnostic obstacles, findings before and after treatment, and reviews previously reported cases of concurrent FSHD and MG. We emphasize the need for clinicians to remain vigilant for the development of symptoms from another rare disease in patients already diagnosed with one, avoiding premature attribution of new symptoms to the baseline condition.